An assessment of coliform and fecal coliform bacteria levels in surface water resources of Bangkok and vicinity area - Thongsri, Tepwitoon; Petchkasem, Surat; Muangkaew, Kanya (Bulletin of Applied Sciences, 2014)
Coliforms and fecal coliform bacteria of surface water resources in Bangkok and vicinity areas were measured and assessed regarding pathogen contamination. 64 samples were taken from the Chao Phraya River, canals, and reservoirs during June to September, 2012. Coliforms and fecal coliform bacteria were enumerated by multiple-tube fermentation technique for members of the coliform group and estimated coliform concentration as MPN index/100 mL. Results indicated that the level of coliform and fecal coliform bacteria measured by MPN was in the range of MPN index/100 ml <1.8 to 1.6 X 107. It was found that 15.6 % of total samples, coliforms and fecal coliforms level was exceeded surface water quality standard class 2. Furthermore, 39 % of total samples, coliforms and fecal coliforms level was exceeded surface water Class 3. Results revealed the overall sanitary quality of selected surface water resources in Bangkok and vicinity areas that the source water may have been contaminated by gastrointestinal pathogens and must be treated and be improved for consuming purposes.